دراسة وتحديد العوامل المؤثرة على نفقات تشغيل النقل العام على المحاور الريفية - داود, شفيق; رستم, أكرم; دغمه, هبه (Latakia University Journal -Engineering Sciences Series, 2018)
تشكل المناطق الريفية قسم كبير من المنطقة الساحلية في سوريا، ويتم الربط بين هذه المناطق وبين مراكز المدن بشبكة من الطرق. تشكل كل من هذه الطرق ووسائط النقل التي تسير عليها نظام النقل الريفي، والذي يتميز بخصائص عامة تتمثل بمستويات منخفضة لكل من حركة المرور والنشاط الاقتصادي وكثافة السكان، وبمسافات طويلة بين المراكز مثل مراكز الخدمة، كما يتميز تقديم الخدمات والعمليات والصيانة بتكاليفها العالية, وغالباً ما تكون هناك ظروف جغرافية وطبيعية صعبة. تعرّف تكاليف تشغيل العربة بأنها التكاليف التي تتنوع مع استخدام العربة، وتشمل هذه التكاليف كل من الوقود، الإطارات، الإصلاح، والصيانة ...الخ، والتي تعتمد على عدد الكيلومترات المقطوعة. خلال الدراسة تمت زيارة وكالات النقل، وورش الصيانة، إضافةً إلى إجراء مقابلات مع عينة عشوائية من سائقي النقل العام العاملين على بعض المحاور الريفية في المنطقة الساحلية، بهدف الحصول على المعلومات المطلوبة حول تكاليف تشغيل المركبة وصيانتها. انتهى البحث بتحديد أهم العوامل التي قد تؤثر على تكلفة تشغيل المركبة على المحاور الريفية (صيانة المركبة، تكاليف الوقود، نوعية الطريق.....)، وباقتراح جملة من التوصيات بهدف تحسين نظام النقل العام ورفع كفاءته في المناطق الريفية. Rural areas form a large part of Syria's coastal area. Linking between these areas and city centers transact of a network of roads. Each of these roads and transport means form the rural transport system which characterized by general characteristics of low levels of traffic, economic activity and population density, and long distances between centers such as service centers. The presenting of services, operations and maintenance characterize at high costs, and there are often difficult geographical and natural conditions. Vehicle operating costs refer to costs that vary with vehicle usage, including fuel, tires, maintenance, repairs…etc., which dependent on the mileage. Transportation agencies and maintenance workshops were visited during this study. As well as, interviews have been done with a random sample of public transport drivers working on some rural axes in the coastal area, in order to obtain the required information about the vehicle operating and maintenance costs. The study concluded by identifying the most important factors that may effect on the tariff of passenger transport on rural axes (maintenance of the vehicle, fuel costs, quality of the road .....) and proposing a number of recommendations aimed at improving the public transport system and raising its efficiency in rural areas